Grover Cleveland's New Foreign Policy - Cleaver, N. author. aut Link
IX, 256 p.
Keywords: Whereas the Spanish-American War has long been studied as a turning point in American history, Grover Cleveland's foreign policy. Nick Cleaver's study illuminates the dynamism and ideals of Cleveland's diplomatic moment, revealing their continuities with the engagement and expansionism of the McKinley presidency.